Uji Aktivitas Kombinasi Ekstrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) Dan Kulit Jeruk Nipis (Citrus aurantifolia) Terhadap Penyembuhan Luka Sayat - Saputri, Naila; Nofita, Nofita; Ulfa, Ade Maria (Jurnal Ilmiah Wahana Pendidikan, 2024)
Plants that are efficacious as wound healers from natural ingredients, namely binahong leaves and lime peel. This study aims to determine the effectiveness of the combination of binahong leaf extract (Anredera cordifolia (Ten.) Steenis) and lime peel (Citrus aurantifolia) on the healing of cuts in male rats (Rattus noervegicus). In the test animal, an incision was made on the back with a length of 2 cm and a wound depth of 0.2 cm using a scalpel (bisturi). The test animals were divided into six treatment groups: normal control without ointment, negative control given ointment base, positive control given povidone iodine ointment, formulation 1 given extract combination ointment (1:3), formulation 2 given extract combination ointment (1:1). , and formulation 3 was given an extract combination ointment (3:1). Ointment is given twice daily for 14 days. Observation of wound healing was carried out by measuring the decrease in the length of the incision in the test animals. The results showed that the combination ointment of binahong leaf extract and lime peel formulation 1 with concentration (1:3) and formulation 2 with concentration (1:1) experienced healing on the 8th day, formulation 3 with concentration (3:1) experienced recovery on day 9. Statistical results using the Mann Whitney HocPost for the F1, F2, and F3 treatment groups compared to the positive control did not have a significant difference because the value obtained was p> 0.05. It was concluded that the combination ointment of binahong leaf extract and lime peel has healing activity for cuts and can be used as a healer for cuts.